ANALISIS KELAYAKAN USAHA DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHATANI JAGUNG PADA LAHAN KERING DAN SAWAH DI KABUPATEN SUMBAWA - Muhammad Nursan (Jurnal Bisnis Tani, 2016)
Maize is one of the mainly crop growth and more cultivated in Indonesia. However, maize Productivity in Indonesia still low both in dry and wetland farming are due to using input factors are not optimally. Therefore, this study aims to: (1) analyze the factors that influence the production of dry and wetland maize farming (2) analyze the level of income of dry and wetland maize farming (3) analyze feasibility of dry and wetland maize farming. Multistage and purposive sampling technique was used to select 70 maize farmers in the study area. Data were collected and the method used are the stochastic frontier production function, Income and R/C ratio analysis. Results showed that variables such as land, seed, fertilizer N, pesticides, and labor had expected signs significantly. The values of R2 of 0.92. The indicated that 92% productions of dry and wetland maize farming affected by inputs on the model, and 8% affected the other inputs. The income of dry and wetland maize farming were each of Rp 9.402.562,78 and Rp 9.172.317,7 with value of R/C ratio were each of 2.02 and 2.19. Therefore, for increase productions of dry and wetland maize farmers have to increase using the inputs such as land, seed, fertilizer N, pesticides, and labor.